Recent Progress in Bio-Responsive Drug Delivery Systems for Tumor Therapy - Cong, Xiufeng; Chen, Jun; Xu, Ran (Frontiers in Bioengineering and Biotechnology, 2022)
Spatially- and/or temporally-controlled drug release has always been the pursuit of drug delivery systems (DDS) to achieve the ideal therapeutic effect. The abnormal pathophysiological characteristics of the tumor microenvironment, including acidosis, overexpression of special enzymes, hypoxia, and high levels of ROS, GSH, and ATP, offer possibility for the design of stimulus-responsive DDS for controlled drug release to realize more efficient drug delivery and anti-tumor activity. With the help of these stimulus signals, responsive DDS can realize controlled drug release more precisely within the local tumor site and decrease the injected dose and systemic toxicity. This review first describes the major pathophysiological characteristics of the tumor microenvironment, and highlights the recent cutting-edge advances in DDS responding to the tumor pathophysiological environment for cancer therapy. Finally, the challenges and future directions of bio-responsive DDS are discussed.